Energy Meter Using a Smartphone - Malik, M.H.A; Kamarudin , M. S. (Evolution in Electrical and Electronic Engineering, 2020)
This project is conducted to establish a monitoring system for electricity consumption that can be controlled via IoT-based protocol enabling consumers to monitor their electricity consumption based on real-time and automatic reading of electricity meters at single-load electrical appliances. The goal of implementing this program is to allow consumers to improve their behaviour in terms of energy use by making efforts to manage electricity demand better and minimize carbon emissions. This device is constructed using NodeMCU, a microcontroller. The programming which contains the code for reading from the current transformer sensor will be submitted to the board of NodeMCU. The programming also includes formulae for measuring energy usage based on TNB’s electricity tariff. The energy consumption information or data will be sent via Wi-Fi to Smartphone apps using the Graphic User Interface. With more excellent timeliness and ease of access for customers or energy suppliers, the program is expected to help customers regulate their electricity consumption.